Performance of sand cement block under axial load with different eccentricity - Amirul Fazlan, Ramli (2011)
The load carrying capacity of structures under eccentric loading is a primary issue for the assessment of several structural elements, such as walls, vaults, arches and pillars. Even though these structures are quite different, they may exhibit a stress concentration resulting from the eccentricity of the load, which may lead to the crushing failure of .the material. From this situation, an experimental works on performance of sand cement block under axial load with different eccentricity were conducted. Three types of block prism namely Prism A, Prism B and Prism C were prepared. All samples were loaded with from the top and both from the top and bottom of block prism with varies of eccentricity which is 0mm, 5mm, 10mm, 15mm and 20mm respectively. Two types of block prism, which is sand cement block and lightweight foam concrete block, (LWFCB) were considered. The ultimate load for Prism A, were I 17.5kN, 77kN, 63.75kN, 56.75kN and 44.5kN through eccentricity of 0mm, 5mm, 10mm, 15mm and 20mm respectively. Whilst, the ultimate load of Prism B was 78.75kN, 72.75kN, 54.75kN, 41.5kN and 30.75kN recorded due to five different eccentricities respectively. Prism C has gained the ultimate load of 43kN, 35.5kN, 1 1.5kN, 7.25kN and 6.25kN when eccentricity increased in 5mm interval respectively. All samples show the same crack pattern which is vertical crack.